Interleukin (IL)-21 promotes intestinal IgA response to microbiota - Cao, Anthony T. (Mucosal Immunol, 2015)
Commensal microbiota-specific Th17 cells are enriched in the intestines, which can convert into Tfh in Peyer’s patches, and are crucial for production of intestinal IgA against microbiota, however, the role of Th17 and Tfh cytokines in regulating the mucosal IgA response to enteric microbiota is still not completely known. In this study, we found that intestinal IgA was impaired in mice deficient in IL-17 or IL-21 signaling. IL-21, but not IL-17, is able to augment B cell differentiation to IgA(+) cells as mediated by TGFβ1, and accelerate IgA class switch recombination (CSR). IL-21 and retinoic acid (RA) induce IgA(+) B cell development and IgA production, and drives autocrine TGFβ1 production to initiate IgA CSR. Repletion of T cell-deficient TCRβxδ(−/−) mice with Th17 cells specific for commensal bacterial antigen, increased levels of IgA(+) B cells and IgA production in the intestine, which was blocked by neutralizing IL-21. Thus, IL-21 functions to strongly augment IgA production under intestinal environment. Furthermore, IL-21 promotes intestinal B cell homing through α(4)β(7) expression, alone or with TGFβ and RA. Together, IL-21 from microbiota-specific Th17 and/or Tfh cells contributes to robust intestinal IgA levels by enhancing IgA(+) CSR, IgA production, and B cell trafficking into the intestine.